Safety index of individual basic sanitation systems in rural area - Scalize, Paulo Sérgio; Bezerra, Nolan Ribeiro; Baracho, Rafaella Oliveira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
The safe access to water and sanitary sewer are human rights, and there is a lack of indexes which evidence if rural areas have safe access levels to these services and others which compose basic sanitation in Brazil. The goal of this work was to elaborate a safety index of rural sanitation at household level, and to apply it in three typologies of rural communities in the state of Goiás: rural settlements, quilombola and riparian communities. For such, the research was developed in five steps: 1) Choice of indicators and sub-indicators; 2) Definition of goals and hierarchical structure; 3) Attribution of due weight to the indicators and sub-indicators; 4) Formulation of the rural sanitation index (ISSRural); and 5) Evaluation of the safety level in 48 rural areas. The proposed ISSRural was composed of six indicators, of which four are associated to basic sanitation components, one is related to habitability conditions and one related to health issues. Four sanitation safe levels have been established, according to the ISSRural score level: Critical, unsafe, partially safe and safe, being that only the last one guarantees the existing sanitation services’ safety. Applying the index in 48 rural areas, none of the communities have reached the “safe” level for the ISSRural and only three areas have reached such level for at least one indicator, which was Rainwater Management. This work proposed an index which has evidenced the safety levels associated to basic sanitation in rural areas, from data at household level, and can be applied with the goal of prioritizing investments, plans and projects which may have greater impact in the population’s sanitation safety, as well as contributing to ensure the human right of access to water and sanitary sewer.